Il mistero della consuetudine. Rileggendo Bobbio filosofo della normatività - Di Lucia, Paolo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
This essay aims to investigate the theory of customary law formulated by the Italian philosopher Norberto Bobbio in the book La consuetudine come fatto normativo (1942). In the first part, the author of the essay reconstructs the main theses of Bobbio’s book and deepens its philosophical and doctrinal context. In the second part, the author of the essay questions the epistemological status of Bobbio’s theory (What is Bobbio’s theory of customary law of?) and asks himself, in the light of Bobbio’s main theses, whether it is possible to investigate the normativity of customary law using the categories and concepts of statutory law and legislative law.